Multiple infections caused by white spot syndrome virus and Enterocytozoon hepatopenaei in pond‐reared Penaeus vannamei in India and multiplex PCR for their simultaneous detection. Issue 3 (18th January 2019) - Thamizhvanan, S.; Sivakumar, S.; Santhosh Kumar, S.; Vinoth Kumar, D.; Suryakodi, S.; Balaji, K.; Rajkumar, T.; Vimal, S.; Abdul Majeed, S.; Taju, G.; Sahul Hameed, A. S.
Abstract: White leg shrimp, Penaeus vannamei, were collected on a monthly basis from grow‐out ponds located at Tamil Nadu and Andhra Pradesh states along the east coast of India for screening of viral and other pathogens. Totally 240 shrimp samples randomly collected from 92 farms were screened for white spot syndrome virus (WSSV), infectious hypodermal and haematopoietic necrosis virus (IHHNV), infectious myonecrosis virus (IMNV) and Enterocytozoon hepatopenaei (EHP). The number of shrimp collected from shrimp farms ranged from 6 to 20 based on the body weight of the shrimp. All the shrimp collected from one farm were pooled together for screening for pathogens by PCR assay. Among the samples screened, 28 samples were WSSV‐positive, one positive for IHHNV and 30 samples positive for EHP. Among the positive samples, four samples were found to be positive for both WSSV and EHP, which indicated that the shrimp had multiple infections with WSSV and EHP. This is the first report on the occurrence of multiple infections caused by WSSV and EHP. Multiplex PCR (m‐PCR) protocol was standardized to detect both pathogens simultaneously in single reaction instead of carrying out separate PCR for both pathogens. Using m‐PCR assay, naturally infected shrimp samples collected from field showed two prominent bands of 615 and 510 bp for WSSV and EHP, respectively.